ANALISIS PENGARUH CONTENT MARKETING, DIGITAL PROMOTION DAN BRAND TRUST TERHADAP REPURCHASE INTENTION KONSUMEN SHOPEE INDONESIA - Kushariyadi Kushariyadi; Vivid Violin; Ichwan Rahmanu Widjaja; Fedianty Augustinah; Muhamad Risal Tawil; Saipul Al Sukri (POLITEKNIK LP3I JAKARTA, 2025)
Repurchase is an important indicator that a bond has been established between the product brand and customer trust. Over time, repurchase behavior can lead to consumer loyalty. Positive experiences that consumers have after using a particular product or receiving quality service help to build emotional bonds and trust. These elements become crucial when consumers decide to make future purchases to fulfill their needs and desires. This research is qualitative in nature, involving interviews and analysis of the influence of each independent variable—namely content marketing, digital promotion, and brand trust—on repurchase intention. The study involved 30 respondents who are Shopee consumers in Indonesia. The results indicate that content marketing, digital promotion, and brand trust all have an influence on repurchase intention. The recommendation for company management is to provide training to enhance competence, innovation, and creativity, especially for the digital marketing team, so they are capable of designing high-quality digital content that can also be used effectively for digital promotional activities. Another suggestion is to tighten the system related to product and service quality, in order to build consumer trust in the brand.